2020
DOI: 10.1108/ijem-02-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the motivational scale for commitments toward teachers’ turnover intentions using self-determination theory: a case of higher education institutions in Pakistan

Abstract: PurposeThis paper aims to demonstrate the turnover intentions (TIs) among the academic faculty of higher education institutions (HEIs) in Pakistan through their motivation and commitment toward the concerned institution. It inspects the relationship of dimensions of motivation including an absence of motivation (AM), extrinsic motivation (ExM) and intrinsic motivation (InM) with the dimensions of commitment including affective commitment (AC), continuous commitment (CC) and normative commitment (NC) and finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 57 publications
(81 reference statements)
3
15
0
Order By: Relevance
“…These results reflect the OCB definition provided by Ahmad (2018). Maryam et al. (2020) is their research found that motivation influences the level of commitment that resultantly affects the turnover intentions of academicians.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…These results reflect the OCB definition provided by Ahmad (2018). Maryam et al. (2020) is their research found that motivation influences the level of commitment that resultantly affects the turnover intentions of academicians.…”
Section: Discussionsupporting
confidence: 76%
“…It adds to the limited research on talent management of senior academics in private universities. Similar research has been conducted by Maryam et al. (2020) in Pakistan and by Wang et al.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations